Where We Read From Matters: Disciplinary Literacy in a Ninth-Grade Social Studies Classroom - Damico, James; Baildon, Mark; Exter, Marisa; Guo, Shiau-Jing (Journal of adolescent & adult literacy, 2009)
Four classes of ninth‐grade students in an international school in East Asia used a set of web‐based technology tools to evaluate two competing webpages about the Taiwan Straits. The findings highlight the ways these students developed disciplinary literacy in social studies by drawing upon cultural resources and contextual knowledge as they responded to and evaluated the claims and evidence within the two texts. Implications of this work point to the potential benefits of educators being more explicit about the relationship between metacognitive reading strategies and the metadiscursive skills that are part of the social studies. A related implication for practice is the need to guide students in discussing, comparing, and contrasting the cultural and contextual knowledge they use to make sense of different texts. لقد استخدمت أربع غرف صف من طلاب الصف التاسع في مدرسة دولية في آسيا الشرقية مجموعة الأدوات التقنية على الشبكة العالمية لتحليل موقعين متنافسين بشأن مديق تاوان. وتسلط النتائج الضوء على الطرق التي طور من خلالها هؤلاء الطلاب معرفة القراءة والكتابة في مجال الدراسات الاجتماعية بواسطة استخدام الموارد الثقافية والمعرفة السياقية حين أجابوا وحللوا الادعايات والأدلة في النصين. وتشير أعقاب هذا العمل إلى الفوائد المحتملة في حالة يكون المعلمون أوضح تجاه العلاقة بين إستراتيجيات القراءة ما وراء المعرفة والمهارات ما وراء الخطاب التي تكوّن جزءاً من الدراسات الاجتماعية ويوجد هناك عاقبة متعلقة بالممارسة وهي الحاجة لتوجيه الطلاب في النقاش حول المعرفتين الثقافية والسياقية والقيام بمقارنتها ومفارقتها التي يستخدمونها كي يفهموا النصوص المختلفة. 在东南亚一所国际学校就读的四班九年级的学生，利用一套以网络为主的科技工具来评估两个有关台湾海峡的相互竞争网站。研究结果凸显出这些学生在回应与评估该两个网站文本所提出的声称与证据时，如何利用文化资源与语境知识来增强他们社会科的学科知识。这项研究的启示就是：教育工作者如果能以更明确的态度，去处理社会科所涉及的元认知阅读策略与元语篇技能之间的关系，学生便可得到其潜在的裨益。另一个相关的教学实践启示就是，教育工作者需要指导学生讨论、比较及对比他们用以理解不同文本的文化与语境知识。 Quatre classes de neuvième année d'une école internationale en Asie du Sud‐Est ont utilisé un ensemble d'outils technologiques basés sur la Toile pour évaluer des pages web traitant des détroits de Taïwan. Les résultats mettent en évidence de quelle façon ces élèves ont développé une littératie disciplinaire en sciences sociales en se basant sur des ressources culturelles et des connaissances contextuelles lorsqu'ils ont répondu en faisant face à la demande et aux données des deux textes. Les implications de ce travail montrent le bénéfice potentiel qu'il y aurait pour les enseignants à être plus explicites quant aux relations entre les stratégies métacognitives de lecture et les compétences métadiscursives qui sont partie intégrante des études sociales. L'implication pratique est la nécessité de guider les étudiants pour discuter, comparer, et contraster les connaissances culturelles et contextuelles qu'ils utilisent pour donner du sens à des textes différents. Четыре девятых класса в международной школе в Юго‐Восточной Азии провели оценку двух конкурирующих вебсайтов, посвященных Тайваньским проливам, используя для этого определенный интернет‐инструментарий. Авторы демонстрируют, как девятиклассники реагировали на содержание текстов и анализировали приводимые в них доводы – то есть читатель получает наглядное представление о том, что дисциплинарная грамотность в социальных науках развивается на основе национально‐культурных ресурсов и контекстного знания. Данное исследование подсказывает, что педагогам следует более открыто и сознательно опираться на связи, существующие между метакогнитивными стратегиями, которые используются при обучении чтению, и метадискурсивными навыками, которые обретаются при изучении социальных наук. Вывод для учителей‐практиков состоит в следующем: надо бережно вести учеников, помогая им – при постижении смысла различных текстов – выстраивать культурное и контекстное знание путем обсуждения, сравнения и противопоставления. Cuatro salones de estudiantes de noveno grado en una escuela internacional en Asia Oriental usaron medios tecnológicos de la red para evaluar dos páginas competidoras de los Taiwán Straits. Los resultados muestran las maneras en que estos estudiantes desarrollaron competencias disciplinarias en las ciencias sociales al usar recursos culturales y conocimiento del contexto a medida que respondían y evaluaban las afirmaciones y la evidencia en ambos textos. Los resultados de este trabajo apuntan hacia los posibles beneficios de hacer que los maestros expliquen claramente la relación entre las estrategias metacogniscitivas de la lectura y las habilidades metadiscursivas que son parte de los estudios sociales. Otra consecuencia a la práctica es la necesidad de guiar a los estudiantes en la discusión, en la comparación, y en la oposición del conocimiento de los contextos que usan al buscar el sentido de los diferentes textos.